Manufacturing Consent Over Statehood Recognition: The New York Times Coverage Of Palestine And Kosovo Statehood Recognition - Qasem, Amer F. S. (2019)
The mainstream media in democratic societies play a key role in shaping the audience perceptions, especially in relation to international affairs. They have the ability to “manufacture” the public consent over the state’s foreign policies. Recognizing or opposing an emerging state is deemed one significant policy at the agenda of governments’ diplomatic foreign affairs. Still, the international recognition by superpower states (i.e. the United States) is influential. The U.S. foreign policy of Palestine and Kosovo statehood recognition constitutes a clear example of the administration’s double standards. Although both states fulfil the minimum criteria of statehood, the U.S. opposes the recognition of the State of Palestine and supports Kosovo’s one. This research examines how the New York Times (NYT)—as a dominant U.S. media—manufactures consent pertaining to the U.S. foreign policy of statehood recognition. The current research employs the Propaganda Model of Herman and Chomsky (1988) as a theoretical thrust. It examines the occurrence of both reporting and ideological biases. Subsequently, three variables are investigated: the degree of reliance on U.S. official news sources; the degree of attention paid to issues under scrutiny; and the representation of the social actors and practices within the related discourse. Both quantitative content analysis and Critical Discourse Analysis (CDA) are adopted. The findings demonstrate that the NYT has offered a fake balance of voices within its related coverage.